Phytophagous insects in peach palm (Bactris gasipaes K.) grown for heart of palm production. - Arroyo-Oquendo, Carlos; Mexzón, Ramón G.S; Mora-Urpí, Jorge (Agronomía Mesoamericana, 2004)
An evaluation of the populations of phytophagous insects present in a variety trial of peach palm for heart of palm productions, was carried out in a locality of the Caribbean region of Costa Rica. Nine species of insects were identified: a. stem borers: Metamasius hemipterus y Rhynchophorus palmarum; b. defoliators: Conocephalus sp., Neoconocephalus sp., Schistocerca pos. nitens y Saliana pos. severus, and c. foliar rasping insects: Demotispa pos. pallida y Cephaloleia sp. In addition, the nests of the ant Solenopsis geminata associated with the basal section of the stem were counted. None of those species reached a level of economic importance and their populations did not show important changes throughout the time of the study. But, during those 12 months the relative abundance of the insects was higher in the spineless varieties than in the spiny one, which is the traditional commercial variety. Some of those insects could become a plague under unusual environmental changes which stress the plants and favor their multiplication. For that reason it is convenient to monitor them to avoid surprises.